Development of Core Outcome Sets for trials on the management of Atrial fiBrillAtion in Critically Unwell patientS (COS-ABACUS): a protocol - Gregory Y H Lip; Bronagh Blackwood; Brian Johnston; Ruaraidh A Hill; Ingeborg D Welters (BMJ Open)
Introduction Atrial fibrillation (AF) is the most common cardiac arrhythmia in critically unwell patients. New-onset AF (NOAF) affects 5%–11% of all admissions and up to 46% admitted with septic shock. NOAF is associated with increased morbidity, mortality and healthcare costs. Existing trials into the prevention and management of NOAF suffer from significant heterogeneity making comparisons and inferences limited. Core outcome sets (COS) aim to standardise outcome reporting, reduce inconsistency between trials and reduce outcome reporting bias. We aim to develop an internationally agreed COS for trials of interventions on the management of NOAF during critical illness.Methods and analysis Stakeholders including intensive care physicians, cardiologists and patients will be recruited from national and international critical care organisations. COS development will occur in five stages: (1) Outcomes included in trials, recent systematic reviews and surveys of clinician practice and patient focus groups will be extracted. (2) Extracted outcomes will inform a two-stage e-Delphi process and consensus meeting using Grading of Recommendations Assessment, Development and Evaluation methodology. (3) Outcome measurement instruments (OMIs) will be identified from the literature and a consensus meeting held to agree OMI for core outcomes. (4) Nominal group technique will be used in a final consensus meeting to the COS. (5) The findings of our COS will be published in peer-reviewed journals and implemented in future guidelines and intervention trials.Ethics and dissemination The study has been approved by the University of Liverpool ethics committee (Ref: 11 256, 21 June 2022), with a formal consent waiver and assumed consent. We will disseminate the finalised COS via national and international critical care organisations and publication in peer-reviewed journals.